Digital Diaspora: A Race for Cyberspace - Everett, Anna (SUNY Press, 2009)
Traces the rise of black participation in cyberspace.Deftly interweaving history, culture, and critical theory, Anna Everett traces the rise of black participation in cyberspace, particularly during the early years of the Internet. She challenges the problematic historical view of black people as quintessential information-age outsiders or poster children for the digital divide by uncovering their early technolust and repositioning them as eager technology adopters and consumers, and thus as coconstituent elements in the information technology revolution. She offers several case studies that include lessons learned from early adoption of the Internet by the Association of Nigerians Living Abroad and their Niajanet virtual community, the grassroots organizing efforts that led to the phenomenally successful Million Woman March, the migration of several historic black presses online, and an interventionist critique of race in contemporary video games. Ultimately, Digital Diaspora shows how African Americans and African diasporic peoples developed the necessary technomastery to ride in the front of the bus on the information superhighway.Anna Everett is Professor of Film and Media Studies at the University of California, Santa Barbara. Her books include Learning Race and Ethnicity: Youth and Digital Media; New Media: Theories and Practices of Digitextuality; and Returning the Gaze: A Genealogy of Black Film Criticism, 1909–1949.
Google-Books-ID: T3xhglJ1_bcC
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Learning Race and Ethnicity: Youth and Digital Media - Everett, Anna (The MIT Press, 2008)
An exploration of how issues of race and ethnicity play out in a digital media landscape that includes MySpace, post-9/11 politics, MMOGs, Internet music distribution, and the digital divide.
Section: 1 v. (IX-197 p.) : illustrations ; 27 cm
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé